DUKUNGAN PERAWAT DENGAN TINGKAT KECEMASAN ORANG TUA PASIEN ACUTE LIMPOBLASTIK LEUKEMIA - Sri Mulyani; Mariyam Mariyam; Dera Alfiyanti; Vivi Yosafianti Pohan (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2019)
The unstable condition in children with acute lymphoblastic leukemia (ALL) after the chemotherapy often leads the parents into anxiety, and even panicking when the children condition drops as the effect of the chemotherapy medication. However, the hyper anxiety may affect the children. In this case, the role of nurse to manage parents’ psychological state is significantly needed. One of the efforts to maintain parents’ psychological state is by nurses’ social support. This research was aimed to find out if there was correlation between nurses’ support with the anxiety level among parents of acute lymphoblastic leukemia (ALL) patients at pediatric clinic of RSUP Dr. Kariadi Semarang. It was a descriptive correlative research with cross sectional approach. The study sample was elderly patient with ALL. The research result showed that nurses’ support was mostly inadequate which was at 52.3% and parents’ anxiety level was considered to be mild anxiety with 40.9%. based on Pearson Product Moment correlation, The research can be concluded that there was correlation between nurses’ support with anxiety level of parents of acute lymphoblastic leukemia (ALL) patients at pediatric clinic of RSUP Dr. Kariadi Semarang (p-value = 0.007, r = -0.401). Based on the research, it is suggested for the pediatric nurses to improve caring behavior during the nursing care.